Evaluation of Child-Friendly School Program at the Primary School in the Bantul District, Indonesia: School Preparedness for an International Program - Mastur, S. Nudia; Irfan; Kramer, Putri; Eveline; Amanina, Nabila; Frisila, Milinia; Lutfiana, Ayun Fitroh (Universitas Negeri Jakarta, 2025)
Background Despite collaborative endorsements by UNICEF and the Indonesian government to actualize child-friendly schools, substantial disparities persist regarding implementation efficacy, particularly within elementary education in the Bantul District. Purpose This study evaluates the execution of the child-friendly school initiative, aiming to delineate its specific impacts on parental cognitive and attitudinal shifts, institutional culture, and pedagogical practices Design/method/approach Employing a quantitative evaluation framework, empirical data were systematically gathered from 795 respondents across 16 primary schools in the Bantul District. The dataset was subsequently subjected to statistical analysis utilizing IBM SPSS Statistics 26 Results Findings demonstrated robust programmatic compliance, with all evaluated institutions surpassing a 75% achievement threshold. The analytical breakdown revealed strong mean scores across all evaluative parameters: 89.64% for context, 81.79% for input, 91.22% for process, and 86.37% for product Contribution/value This research elucidates the localized impacts of macro-level child-friendly educational policies, offering a verifiable assessment framework to help policymakers and educators optimize institutional environments, teaching methodologies, and community engagement